Phosphorylation of CAD1, PLDdelta, NDT1, RPM1 Proteins Induce Resistance in Tomatoes Infected by Ralstonia solanacearum - Prachumporn Nounurai; Anis Afifah; Suthathip Kittisenachai; Sittiruk Roytrakul (Plants, 2022)
Ralstonia solanacaerum is one of the most devastating bacteria causing bacterial wilt disease in more than 200 species of plants, especially those belonging to the family Solanaceae. To cope with this pathogen, plants have evolved different resistance mechanisms depending on signal transduction after perception. Phosphorylation is the central regulatory component of the signal transduction pathway. We investigated a comparative phosphoproteomics analysis of the stems of resistant and susceptible tomatoes at 15 min and 30 min after inoculation with Ralstonia solanacearum to determine the phosphorylated proteins involved in induced resistance. Phosphoprotein profiling analyses led to the identification of 969 phosphoproteins classified into 10 functional categories. Among these, six phosphoproteins were uniquely identified in resistant plants including cinnamyl alcohol dehydrogenase 1 (CAD1), mitogen-activated protein kinase kinase kinase 18 (MAPKKK18), phospholipase D delta (PLDDELTA), nicotinamide adenine dinucleotide transporter 1 (NDT1), B3 domain-containing transcription factor VRN1, and disease resistance protein RPM1 (RPM1). These proteins are typically involved in defense mechanisms across different plant species. qRT-PCR analyses were performed to evaluate the level of expression of these genes in resistant and susceptible tomatoes. This study provides useful data, leading to an understanding of the early defense mechanisms of tomatoes against R. solanacearum.